Notes and order of the Freudian text on the «Rat Man» within a Lacanian framework - Asensi Pérez, Manuel (2024)
In the following pages, we propose to organise and connect the different parts that make up Freud’s text A propósito de un caso de neurosis obsesiva (el Hombre de las ratas) from a Lacanian perspective. Freud’s writing, at times, gives the impression of accumulating ideas about obsessional neurosis, without the connection between them always being clear. In the introduction, Freud himself warns that his work consists of ‘fragmentary communications’, and this analysis seeks to link these fragments together. Furthermore, it traces the path that has allowed the Lacanian reading of Freud, although, without going into this aspect in depth, it leaves open the possibility of addressing it in future studies.